Effects of thermal and electric fields on soybean trypsin inhibitor protein: A molecular modelling study. (June 2016) - Harish Vagadia, Brinda; Vanga, Sai Kranthi; Singh, Ashutosh; Raghavan, Vijaya
Abstract: This study uses molecular dynamics (MD) simulations in investigating the unusual stability of Soybean Trypsin Inhibitor (STI) protein. The effects of temperature and oscillating electric fields (0.5 V/nm and 2.45 GHz) have been used to perform simulations using GROMACS software. The conformational changes in the protein were studies using root mean square deviations and secondary structure analysis (STRIDE). It was found that significant rearrangements took place within the protein especially in 'turns' and 'coils', but the core structure was stable under external stresses because of the antiparallel β-sheet structure. This study also provides evidence that the aromatic residues play a major role in stabilizing the STI protein using Solvent Accessible Surface Area (SASA) analysis. Ramachandran plots were also used to analyze the stability of the molecules obtained on treatment with temperatures (300 K to 393 K) and oscillating electric fields. Industrial relevance: Molecular dynamics (MD) simulation techniques have been applied to visualize and predict the behaviour of proteins during food processing, and changes in their structure under the influence of external field stress. This study can be used to understand the changes at molecular level that could help industrialists to design processing methods with increased nutritive and sensory appeal of food products. This work can also contribute to the optimization of process parameters to enhance the functional properties of protein and increase protein digestibility. Highlights: Structural changes in Soybean Trypsin Inhibitor (STI) protein under the external field stress were visualized by Molecular Dynamics (MD) simulation techniques. Conformational changes in the STI protein structure were observed using secondary structure analysis (STRIDE) and Root Mean Square Deviation (RMSD) analysis. Solvent Accessible Surface Area (SASA) analysis showed visible changes in the secondary structure of the protein. Ramachandran plots were used to evaluate the stability of the molecules obtained on treatment with different processing conditions.